Productivity, profitability and financial fragility: Empirical evidence from Italian business firms - Giulio Bottazzi; Angelo Secchi; Federico Tamagni (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2007)
In this work we investigate two crucial dimensions of firms' structure and dynamics, that is profitability and productivity performance. The empirical distributions and the associated persistence over time are explored through a set of parametric and non parametric exercises performed on an large panel of Italian firms active in both Manufacturing and Services during the period 1998-2003. The main contribution resides in the use of an index of financial risk which allows us to document that not obvious interactions are in place among economic performances, financial conditions and availability of external credit. We also offer an initial understanding about how profitability and productivity relate with a third dimension of performance, that is firm growth. We find that, independently from the particular sector of activity and from financial conditions, there seems to be little market pressure and little behavioral inclination for the more efficient and more profitable firms to grow faster.
Keywords: C14; D21; D24; L25; G30; 330; firm performance; profitability; productivity; financial constraints; Produktivität; Rentabilität; Unternehmenserfolg; Betriebliche Kennzahl; Italien